Nine per cent nickel : 28 years of reliable service in liquefied natural gas containment - Mounce, William S. (Nickel Institute, 1989)
A five-year multinational study sponsored by the Gas Research Institute (GRI) has shown in quantitative terms that 9% nickel steel has very high resistance to the initiation and propagation of brittle fracture at liquid natural gas (LNG) temperatures.This publication reviews the practical significance of the GRI studies to the designers and owners of liquefied natural gas facilities, and relates them to the unblemished record that the steel has compiled since the early 1960s in ship and storage tanks.
Keywords: Liquefied natural gas -- Storage.; Liquefied natural gas -- Transportation.; Nickel steel -- Industrial applications.; elektronické knihy; electronic books